Endogenous Colonial Institutions: Lessons from Fiscal Capacity Building in British and French Africa, 1880-1940 - Ewout Frankema; Marlous van Waijenburg (African Economic History Network (AEHN), 2013)
Given difficult to access pre-colonial forms of surplus extraction, African colonial governments faced severe constraints to raise revenue for incipient colonial state formation. This paper compares the ways in which the British and the French dealt with this challenge in a quantitative framework. We exploit colonial government budget accounts to construct PPP-adjusted comparisons of per capita government revenue by source. A comparison of fiscal capacity building shows that pragmatic responses to varying local economic, political and demographic conditions can easily be mistaken for specific metropolitan blueprints of colonial governance and that under comparable local circumstances the French and British operated in remarkably similar ways.
Keywords: E62; H11; H20; N25; N27; O10; 330; colonial institutions; fiscal policy